Virtual Screening of Coffea arabica Phytochemicals as Natural β-Lactamase Inhibitors - Nisa, Faiz un; Javid, Amina (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
One of the key contributors to antimicrobial resistance is the enzymatic hydrolysis of β-lactam antibiotics by β-lactamases, becoming one of the leading public health challenges. In order to overcome this issue, the current work utilizes advanced in-silico grid-based molecular docking and post-docking analysis to identify potential β-lactamase inhibitors from Coffea arabica beans. Based on past experimental evidence of coffee’s antimicrobial activity, this research aimed to explore the inhibitory potential of its bioactive compounds through computational modeling to identify natural alternatives to synthetic inhibitors. Seventy-three phytochemicals were then screened and molecularly docked by AutoDock against four clinically relevant β-lactamases, namely, AmpC, CTX-M9, CTX-M14, and SHV-1, and subsequently subjected to toxicity and ADMET analysis. Among these, tannin, epicatechin, quercitrin, and quercetin exhibited the highest binding affinities (-8.5 kcal/mol, -7.7 kcal/mol, -8.6 kcal/mol, and -8.6 kcal/mol, respectively), outperforming the reference inhibitor, Avibactam. ADMET analysis also revealed favorable pharmacokinetic, low toxicity, and oral bioavailability of the top-ranked phytocompounds. Collectively, the results indicate the novelty of C. arabica’s phytochemicals as promising natural β-lactamase inhibitors. However, further in-vitro and in-vivo studies are required for validating their therapeutic efficacy against resistant bacteria. The current study also establishes a framework for integrating computational approaches in phytochemical research to accelerate antibacterial drug discovery.